Home-Based Physical Therapy for Individuals With Stroke in Thailand. (November 2016) - Hiengkaew, Vimonwan; Vongsirinavarat, Mantana
In Thailand, individuals with stroke prefer to return home after being discharged from hospital and most of them have inconveniences to get to hospitals or clinics to receive physical therapy. Thus, home-based physical therapy (HBPT) might be an option. A retrospective pre-test and post-test study was conducted among 2, 412 individuals with first stroke after receiving HBPT. It showed significant ( p < .0001) improvement in voluntary movement, postural balance, and activities of daily living (ADLs) in individuals with after-stroke duration of ≤20 years. Those with after-stroke duration of >20 years demonstrated significant development in voluntary movement ( p = .005) and postural balance ( p = .037), but not ADLs. In conclusion, HBPT improves voluntary movement, postural balance, and ADL in individuals following any period of first stroke, and might be an alternative service for them in Thailand.